The Influence of Promotion, Web Quality, and Electronic Payment (E-Wallet) Convenience Moderated by Positive Emotions on Impulsive Skincare Purchases - Jessica Emanuella (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to examine the effect of promotion, web quality, and ease of electronic payments (E-Wallets) moderated by positive emotions on impulse skincare purchases. Impulse buying is often associated with making relatively faster and instant decisions without requiring a long time to think. Differences of Individual personality can give rise to a wide variety of experiences when making purchases, Lack of control from consumers signifies their inability to delay gratification thus leading to impulse purchases. This study is quantitative research focusing on survey through distributiong questones. This study employes the PLS 4.0 program to examine the data. The population of this study are People at the productive age of work, the age of 17-50 years. This research shows that Promotions and E-Wallets have a positive and significant effect on Impulsive Buying and Web Quality does not have a positive and significant effect on Impulsive Buying. Positive Emotions have a positive and significant effect in mediating Promotions and E-Wallets with Impulsive Buying, and Positive Emotions do not have a positive and significant effect in moderating Web Quality with Impulsive Buying.